The synergistic inhibition and mechanism of epicatechin gallate and Chitosan against Methicillin-resistant Staphylococcus aureus and the application in pork preservation. (15th June 2022) - Guo, Qin; Ren, Cheng-wan; Cai, Jia-hui; Zhang, Chun-yan; Li, Yun-ting; Xu, Bin; Farooq, Muhammad Adil
Abstract: Livestock-associated -Methicillin-resistant S. aureus (LA-MRSA) contamination on pork has emerged as one of the major concerns worldwide. Combinations of natural plant extracts (NPEs) and food preservatives were tested for their anti-MRSA activities. The most effective combination was evaluated using texture profile, physicochemical analysis and sensory quality. The synergistic antibacterial mechanisms were examined using transcriptomic sequencing and electron microscope. Results showed that 1/8 minimal inhibitory concentration (MIC) (−)-epicatechin gallate (ECG) + 1/16 MIC chitosan had the optimum inhibition on the growth of MRSA with FIC of 0.19. The combination extended the shelf life of pork from 5 to 7 d at 4 °C and from 36 h to 48 h at 25 °C based on MRSA challenge test. The combination effectively maintained the hardness, elasticity, cohesion, recovery, and chewiness of pork and delayed the process of spoilage, lipid oxidation, accumulation of free amino acid, and Met Mb of pork contaminated by MRSA. Synergistic antibacterial mechanisms may be associated with improved cell deformation (stickiness and slight shrinkage). Six differentially expressed genes, lrgB and LytM, clfA, icaB, and icaA and blaI were confirmed to be responsible for the synergistic antibacterial mechanisms. Combining ECG with chitosan may be useful food preservatives in the pork industry. Highlights: The combination of ECg + chitosan showed the optimum inhibition on MRSA. The combination extended the shelf life of pork storage at 4 °C and 25 °C treated by MRSA. TPA profile, physicochemical analysis and sensory quality of pork were improved due to the addition of the combination. The synergistic antibacterial mechanisms were related to improved cell deformation. lrgB, LytM, clfA, icaB, icaA and blaI were confirmed to be responsible for the mechanisms.